Back to the future: The growth prospects of transition economies reconsidered - Nauro F. Campos (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2000)
How many years will the average transition economy need to reach the income level of the average OECD country? The favored methodology in use to answer such questions is referred to as the BLR approach, because it uses specifications from Barro, and Levine and Renelt. The literature has so far refrained from identifying and testing the underlying assumptions of the BLR approach. This paper attempts to fill this gap. Our results contrast sharply with the assumptions and findings from the BLR approach, questioning its might and challenging our understanding of the transition process in its key dimension.
Keywords: E23; O40; P20; P52; 330; economic growth; transition economies; growth prospects; Wirtschaftswachstum; Entwicklungskonvergenz; Schätzung; Transformationsstaaten; Osteuropa